LOX Expression and Functional Analysis in Astrocytomas and Impact of IDH1 Mutation - da Silva, Roseli (PLoS One, 2015)
Lysyl oxidase (LOX) is involved in vital biological processes such as cell motility, cell signaling and gene regulation. Deregulation of this protein can contribute to tumor formation and progression. Although it is known that LOX is involved in invasion, proliferation and tumor migration in other types of tumors, studies of LOX in astrocytomas of different grades are scarce. The purpose of our study was to characterize LOX, BMP1 and HIF1A expression by real-time PCR in astrocytomas with WHO grades I to IV compared to non-neoplastic brain tissue. IDH1 mutational status was determined by PCR and sequencing. LOX protein expression was also analyzed by immunohistochemistry. LOX functional analyses were performed using siRNA knockdown and the specific inhibitor BAPN in two glioblastoma cell lines. The expression levels of LOX, BMP1 and HIF1A were correlated and analyzed according to IDH1 mutation status and to the clinical end-point of overall survival of glioblastoma patients. The results demonstrate that increased expression and activity of LOX, BMP1 and HIF1A were positively correlated with the malignant grade of astrocytomas. LOX protein expression also increased according to the degree of malignancy, with localization in the cytoplasm and nucleus and staining observed in endothelial cells. Glioblastoma with a mutation in IDH1 expressed lower levels of LOX in the nucleus, and IDH1-mutated cases showed lower LOX expression levels when compared to wild-type IDH1 cases. LOX knockdown and inhibition by BAPN in U87MG and A172 cell lines affected migration, invasion and soft agar colony formation. Taken together, these results corroborate the role of LOX in the migration, invasion and angiogenesis of astrocytomas. Furthermore, LOX expression is influenced by IDH1 mutational status. This work provides new insights for researchers aiming to design targeted therapies to control astrocytomas.